Chemical fluorescence-based dye staining for 3-dimensional histopathology analysis. Issue 2 (4th March 2022) - Kim, Hyun Jung; Kim, Jeongah; Choi, Jungyoon; Sun, Woong
ABSTRACT: Tissue clearing for 3-dimensional (3D) imaging is increasingly utilized in many biomedical applications, including the pathological examination of human biopsy specimens. Although many protocols offer rapid and efficient tissue clearing (>1 d), immunofluorescence labeling of thick specimens is a highly time-consuming process. The use of low molecular weight chemical dyes has potential benefits in terms of speed and quality of 3D labeling. Accordingly, we tested several chemical dyes to assess their potential applications in 3D imaging. The combination of SYTO 16 and eosin (S&E) was found to be a potential fluorescent version of the hematoxylin–eosin (H&E) stain. Furthermore, picrosirius red (for collagen), Congo red (for senile plaques), and fluorescent Nissl (for neurons in the normal brain or blood vessels in the injured brain) stains can be used alone or in combination with antibody labeling. As chemical labeling requires a relatively short incubation time (<1 d), fluorescent chemical dyes could expedite the 3D imaging process.